Outcome Disparities Between Medical Personnel and Nonmedical Personnel Patients Receiving Definitive Surgery for Colorectal Cancer. Issue 4 (January 2015) - Liu, Chia-Jen; Huang, Nicole; Lin, Chun-Chi; Lee, Yu-Ting; Hu, Yu-Wen; Yeh, Chiu-Mei; Chen, Tzeng-Ji; Chou, Yiing-Jenq; Huo., Jinhai
<x xml:space="preserve">Abstract</x> Abstract Disparities in quality of care have always been a major challenge in health care. Providing information to patients may help to narrow such disparities. However, the relationship between level of patient information and outcomes remains to be explored. More importantly, would better-informed patients have better outcomes through their choice of higher quality providers? We hypothesize that medical professionals may have better outcomes than nonmedical professionals following definitive surgery for colorectal cancer (CRC), and their choice of provider may mediate this relationship. We identified 61, 728 patients with CRC receiving definitive surgery between 2005 and 2011 from the Taiwan National Health Insurance Research Database. Medical professionals were identified via the registry for medical personnel. Indicators for surgical outcome such as emergency room (ER) visits within 30 days, medical expenses, length of hospital stay (LOS), and 5-year mortality were analyzed by using fixed and random effects multivariate regression models. Compared with nonmedical personnel CRC patients, a greater proportion of medical personnel received definitive surgery from higher volume surgeons (median 390 vs 311 within the study period) and/or in higher volume hospitals (median 1527 vs 1312 within the study period). CRC patients who are medical personnel had a shorter median LOS (12 vs 14 days), lower median medical expenses (112, 687 vs 121, 332 New Taiwan dollars), a lower ER visit rate within 30 days (11.3% vs 13.0%), and lower 5-year mortality. After adjusting for patient characteristics, medical personnel had a significantly lower hazard of 5-year mortality, and were significantly more likely to have a LOS shorter than 14 days than their nonmedical personnel counterparts. However, after adjusting for patient and provider characteristics, while medical personnel were significantly less likely to have a long LOS, no significant difference was observed in 5-year mortality between the 2 groups. Medical personnel did have a significantly better survival outcome and a shorter length of stay following definitive surgery than nonmedical personnel patients. The outcome disparities can be partially explained by characteristics of their treatment providers. The findings may serve as an important reference for better understanding how information may narrow gaps in quality of care through better choice of providers.